Constraints Faced by Developmental Personnel Concerning Livelihood Programmes Across Paniya and Kanikkar Tribes, Kerala (Indian Journal of Extension Education, 2025)
The study examined the constraints faced by developmental personnel concerning tribal Livelihood Development Programmes (LDPs) among the Paniya community in Wayanad and the Kanikkar community in Thiruvananthapuram. Data were collected from 120 personnel between January and May 2025 using a structured schedule, and constraints were prioritised using Garrett’s ranking technique. The results showed that excessive workload was a major challenge in both regions. However, personnel working with the Paniya community reported greater institutional delays and limited field-level staffing, while those working with the Kanikkar community faced stronger political influence and poor transport connectivity. Limited exposure to indigenous knowledge and seasonal migration of household head were notable socio-cultural barriers in both contexts. The findings underline that operational constraints faced by developmental personnel vary across tribal settings and are shaped by administrative, socio-cultural, and infrastructural factors. Addressing these constraints through context-specific planning, improved institutional coordination, and strengthened field-level support is essential for enhancing the effectiveness of livelihood interventions in tribal areas.